2009
DOI: 10.1111/j.1476-5381.2009.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C: update on physiology and pharmacology

Abstract: Although ascorbic acid is an important water-soluble antioxidant and enzyme cofactor in plants and animals, humans and some other species do not synthesize ascorbate due to the lack of the enzyme catalyzing the final step of the biosynthetic pathway, and for them it has become a vitamin. This review focuses on the role of ascorbate in various hydroxylation reactions and in the redox homeostasis of subcellular compartments including mitochondria and endoplasmic reticulum. Recently discovered functions of ascorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
283
1
22

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(311 citation statements)
references
References 183 publications
(185 reference statements)
5
283
1
22
Order By: Relevance
“…Only few studies have monitored concentrations and vitamin C supplementation in saliva [17,39,42,43,45,47]. Requirement for vitamin C is in humans satisfied by the ordinary diet [29]. Our results have shown that vitamin C supplementation led to significantly decreased carbonyl stress and increased antioxidant status.…”
Section: Effect Of Vitamin Csupporting
confidence: 68%
“…Only few studies have monitored concentrations and vitamin C supplementation in saliva [17,39,42,43,45,47]. Requirement for vitamin C is in humans satisfied by the ordinary diet [29]. Our results have shown that vitamin C supplementation led to significantly decreased carbonyl stress and increased antioxidant status.…”
Section: Effect Of Vitamin Csupporting
confidence: 68%
“…Th e biological viability of vitamin C reduces over time. [5] Th e metabolism of vitamin C starts from the oral buccal mucosa by means of passive diff usion. In the gastrointestinal system, the absorption is through an energy expenditure and carrier-mediated transport mechanism.…”
Section: Metabolism Of Vitamin Cmentioning
confidence: 99%
“…Vitamin C (vit C) is an essential dietary nutrient in humans that is involved in a wide range of biological processes including collagen biosynthesis, as a cofactor of several enzymes, facilitating iron transport and as a physiological antioxidant (Mandl et al, 2009). Studies have described the beneficial effects of vit C in treating human and experimental TB (McConkey & Smith, 1933;Hemila et al, 1999).…”
Section: Introductionmentioning
confidence: 99%